Targeting the JAK-STAT pathway in colorectal cancer: mechanisms, clinical implications, and therapeutic potential - Li, Penghui; Huang, Di (Frontiers in Cell and Developmental Biology, 2024)
Colorectal cancer (CRC) remains one of the most prevalent and fatal malignancies worldwide, consistently ranking among the top three in terms of incidence and mortality. Despite notable advancements in early detection and therapeutic interventions, survival outcomes for advanced-stage CRC are still dismal, largely due to issues such as drug resistance and metastasis. Recent research has increasingly implicated the JAK-STAT signaling pathway as a pivotal contributor to CRC pathogenesis. This evolutionarily conserved pathway plays a key role in transmitting extracellular signals to the nucleus, thereby modulating gene expression involved in numerous fundamental biological processes. In CRC, dysregulation of the JAK-STAT pathway is frequently observed and is strongly associated with tumor progression, including processes such as cellular proliferation, apoptosis, metastasis, immune evasion, and the sustenance of cancer stem cells. Given its integral role in CRC advancement, the JAK-STAT pathway has gained recognition as a viable therapeutic target. Extensive evidence from preclinical and clinical models supports the efficacy and safety of targeting components of the JAK-STAT pathway, presenting new therapeutic possibilities for patients with CRC, particularly in addressing drug resistance and enhancing treatment outcomes. This review offers a detailed exploration of the JAK-STAT pathway, focusing on its regulatory mechanisms in CRC-related malignancies. Moreover, it examines the association between JAK-STAT protein expression, clinical features, prognosis, and its therapeutic potential in CRC management.